THE AESTHETIC RECONSTRUCTION OF POST-BURN EYEBROW ALOPECIA WITH BILATERAL SUPERFICIAL TEMPORAL ARTERY ISLAND SCALP FLAP - Suman, Dhirendra; Kumar, Yashvinder; Tayal, Anish; Nadikuditi, Sumathi (Journal of Ayub Medical College Abbottabad, 2024)
Plastic surgeons face unique challenges in reconstructing eyebrows due to their complex anatomy and gender variations. We report a case of a 16-year-old female who presented with post-burn bilateral eyebrow alopecia. Bilateral eyebrow reconstruction was performed with scalp island flaps based on the posterior branch of the superficial temporal artery, which showed good postoperative outcomes. This case showed that the superficial temporal artery island flap continues to be a versatile option for managing eyebrow alopecia, especially in cases of deep burns of the face.